Impact of Subsequent Treatment on Clinical Outcomes in Patients with EGFR-Mutant Non-Small Cell Lung Cancer Transformed to Small-Cell Lung Cancer - Chen CY; Ko HW; Hu PW; Chang CY; Chen CY; Chang SC; Chiu YC; Wei YF (Lung Cancer: Targets and Therapy)
Ching-Yi Chen,1,2 How-Wen Ko,3 Po-Wei Hu,4 Cheng-Yu Chang,5,6,* Chung-Yu Chen,7,* Shih-Chieh Chang,4,* Yu-Chi Chiu,8,* Yu-Feng Wei9,* 1Division of Chest Medicine, Department of Internal Medicine, E-Da Hospital, I-Shou University, Kaohsiung, Taiwan; 2College of Medicine, I-Shou University, Kaohsiung, Taiwan; 3Division of Pulmonary Oncology, Department of Thoracic Medicine, Linkou Chang Gung Memorial Hospital, Chang Gung University, College of Medicine, Taoyuan, Taiwan; 4Division of Chest Medicine, Department of Internal Medicine, National Yang-Ming Chiao Tung University Hospital, Yi-Lan, Taiwan; Faculty of Medicine, College of Medicine, National Yang-Ming Chiao Tung University, Taipei, Taiwan; 5Division of Chest Medicine, Department of Internal Medicine, Far Eastern Memorial Hospital, New Taipei City, Taiwan; 6Department of Electrical Engineering, Yuan Ze University, Taoyuan City, Taiwan; 7Department of Internal Medicine, National Taiwan University Hospital Yunlin Branch, Yunlin County, Taiwan; College of Medicine, National Taiwan University, Taipei, Taiwan; 8Department of Internal Medicine, Taoyuan General Hospital, Ministry of Health and Welfare, Taoyuan, Taiwan; 9Department of Internal Medicine, E-Da Cancer Hospital, Kaohsiung, Taiwan; School of Medicine for International Students, College of Medicine, I-Shou University, Kaohsiung, Taiwan*These authors contributed equally to this workCorrespondence: Yu-Feng Wei, Department of Internal Medicine, E-Da Cancer Hospital, No. 1, Yida Road, Jiao-Su Village, Yan-Chao District, Kaohsiung, 824, Taiwan, Email yufeng528@gmail.comPurpose: In epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) patients treated with EGFR-tyrosine kinase inhibitors (TKIs), transformation to small-cell lung cancer (SCLC) is associated with poor outcomes, and the optimal treatment strategy is unclear. This study aimed to investigate the clinical factors and treatments associated with outcomes in this group.Patients and Methods: This retrospective multicenter study enrolled patients with SCLC transformed from advanced NSCLC after progression on EGFR-TKI treatment. We analyzed clinical and demographic characteristics, first-line EGFR-TKI treatments, and subsequent regimens to identify factors associated with clinical outcomes.Results: Twenty-seven patients diagnosed with SCLC transformation after EGFR-TKI therapy between 2018 and 2023 were enrolled, most of whom had an EGFR exon 19 deletion (67%). The subsequent treatment regimens included traditional chemotherapy (CT) in 12 patients (44%), combined CT/EGFR-TKI in 10 patients (37%), and combined CT/immunotherapy in 5 patients (19%). The median progression-free survival (PFS) with first-line EGFR-TKI treatment, subsequent SCLC treatment, and overall survival (OS) were 16.1 months, 6.4 months, and 39.5 months, respectively. The overall response rate (ORR), disease control rate (DCR), and median PFS for subsequent treatments were 38.5%, 69.2%, and 6.4 months, respectively. The DCRs for subsequent CT, CT/TKI, and CT/immunotherapy were 41.7%, 88.9%, and 100%, respectively. ORR and PFS were higher in the CT/TKI (44.4% and 7.2 months) and CT/immunotherapy (80.0% and 11.3 months) groups compared to CT (16.7% and 3.7 months), but these differences were not statistically significant. Univariate and multivariate analyses showed no significant differences in PFS and OS among treatments.Conclusion: In patients with SCLC transformed from advanced NSCLC after EGFR-TKI treatment, adding immunotherapy and EGFR-TKI to CT improved DCR and showed trends in ORR and PFS, but did not provide an OS benefit. More prospective studies with varied therapeutic approaches are needed to confirm these findings.Keywords: EGFR-mutant NSCLC, SCLC transformation, EGFR-TKI, chemotherapy, immunotherapy, clinical outcomes